Auto Berthing – a Solution for Achieving Zero Waiting Time at Harbour - Aulia Siti Aisjah; A A Masroeri; Aries Sulisetiyono; Randika Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Tanjung Perak Port is one of biggest harbour in Indonesia. The shipping start from Karang Jamuang to Naval Base. The moving is use help of scout ships and tug boat. A control system can be applied to anchored ships , to replace the role of tug and scout boat. Movement from the parking position to the anchored involve auto maneuver and auto berthing. Both auto system is designed using fuzzy logic control. Input of control from sensors and guidance according to the path leading to the dock, and to anticipate the environmental disturbance factors (that is ocean currents). Control rules are unique, according to the type and size of vessel. In the case study to AHTS vessels, berthing auto show good ability. The heading error of 0.04° to the direction parallel to the dock, and the range of distances error is 0.16 to 2.16 meters from the desired position. Reduction of processing time leaning point to Jamrud dock is 33 minutes.